2011
DOI: 10.2522/ptj.20100277
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Psychosocial Factors and Their Association With Knee Pain and Function After Anterior Cruciate Ligament Reconstruction

Abstract: Psychosocial factors are potentially modifiable early after ACL reconstruction. Baseline psychosocial factor levels did not predict knee pain or function 12 weeks postoperatively. Interventions that increase self-efficacy for rehabilitation tasks or decrease fear of movement or reinjury may have potential to improve short-term outcomes for knee pain and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
123
3
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(137 citation statements)
references
References 40 publications
9
123
3
2
Order By: Relevance
“…Including the use of Tampa Scale of Kinesiophobia (TSK-11) [57] will allow the rehabilitation team to identify those individuals with high fear of movement and thus warrant a modification to the therapeutic approach. Through delaying the progression through the protocol, providing education to improve patient self-efficacy, and incorporating neuromuscular re-education techniques such as perturbation training may benefit the patient who exhibits high fear [58,59]. Kinesiophobia and pain catastrophizing are two psychological factors which have been shown to be strongly correlated with lack of return to sport [55].…”
Section: Fearmentioning
confidence: 99%
“…Including the use of Tampa Scale of Kinesiophobia (TSK-11) [57] will allow the rehabilitation team to identify those individuals with high fear of movement and thus warrant a modification to the therapeutic approach. Through delaying the progression through the protocol, providing education to improve patient self-efficacy, and incorporating neuromuscular re-education techniques such as perturbation training may benefit the patient who exhibits high fear [58,59]. Kinesiophobia and pain catastrophizing are two psychological factors which have been shown to be strongly correlated with lack of return to sport [55].…”
Section: Fearmentioning
confidence: 99%
“…We think that a phenomenon of ''overprotection'' of the knee joint develops after surgery on the IL. Psychological factors, such as the fear of reinjury, have been shown to limit the extent of functional recovery after ACL reconstruction 12,22 and, therefore, may limit knee-joint extension. During dynamic movements and given the anatomic constraint, 23 antagonist muscles play the role of ''brakes'' against the movement to protect the joint.…”
Section: Joint Kinematicsmentioning
confidence: 99%
“…Prior studies have reported an association between postoperative self-efficacy and improved functional recovery outcomes among individuals who have undergone hip or knee replacement. 29,31,43 Increased self-efficacy for rehabilitation has been shown to contribute to improved knee function following ACL reconstruction 6 and knee replacement surgery. 23 In the present case, at 9 months post BMAC surgery knee self-efficacy was lower than females 4 months post ACL reconstruction 41 SER score only indicated a moderate belief in ability to perform activities in rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…29,37 The SER was designed specifically for patients undergoing lower limb orthopaedic surgery 45 and has been used in ligament reconstruction 6 and joint replacement 23 but it has not been previously used in a knee osteochondral repair population. The mean SER scores are shown in Figure 2.…”
Section: Self-efficacy For Rehabilitation Outcomes Scale (Ser)mentioning
confidence: 99%